2018
DOI: 10.1186/s12871-018-0613-6
|View full text |Cite
|
Sign up to set email alerts
|

Programmed intermittent epidural bolus versus continuous epidural infusion for postoperative analgesia after major abdominal and gynecological cancer surgery: a randomized, triple-blinded clinical trial

Abstract: BackgroundContinuous epidural infusion (CEI) is the standard application setting for epidural infusion. A new mode, the programmed intermittent epidural bolus (PIEB) technique, showed reduced local anesthetic (LA) consumption and improved analgesia in obstetric analgesia. Goal of this trial was to evaluate the effects of PIEB versus CEI [combined with patient-controlled bolus (PCEA)] on LA consumption and pain scorings in major abdominal cancer surgery.MethodsFollowing ethical approval, patients scheduled for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…The reduction in the total amount of local anesthetic with intermittent bolus infusion compared with continuous infusion is consistent with the findings in labor analgesia reports and postoperative reports. In major abdominal and gynecological surgery, the beneficial effect of PIB is noted on the first postoperative day and not on the day of the operation [9]. Sequential epidural bolus infusion provides superior epidural block compared with CEI [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduction in the total amount of local anesthetic with intermittent bolus infusion compared with continuous infusion is consistent with the findings in labor analgesia reports and postoperative reports. In major abdominal and gynecological surgery, the beneficial effect of PIB is noted on the first postoperative day and not on the day of the operation [9]. Sequential epidural bolus infusion provides superior epidural block compared with CEI [2].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the incidence of hypotension, the difference between our results and those of previous reports might be associated with differences in the site of epidural anesthesia and dose of local anesthetic. Hypotension occurred but was not significant in both groups, and there was a need for noradrenalin when epidural anesthesia involved puncture at Th8–10 [9]. On the other hand, when epidural anesthesia involved puncture at Th10–12 in open gynecological surgery [8] or L3–5 in total knee arthroplasty, [8] there was no hypotension requiring intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of different pain entities and the target spinal level in major abdominal surgery compared with labor analgesia, the clinical application of PIEB in abdominal surgery might be limited. Few studies have compared the use of PIEB versus CEI after major abdominal surgery, [7,8] and two studies showed inconsistent postoperative outcomes. One study showing the difference between the two groups reported that the PCEA bolus needs were decreased in the PIEB group.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the anesthetic regimens of both, combined GA and EA and general anesthesia alone (systemic analgesia) deviate significantly regarding substance use, mode of application (bolus vs. continuous; provider‐controlled vs. patient‐controlled) and timing of EA initiation 6 . Indeed, there is a wide range of possible variation within combined GA and EA and although some aspects have been addressed in trials and meta‐analyses, 13–16 guidelines on the optimal performance do not exist. Recently, The Royal College of Anaesthetists published an updated version of their “Best practice recommendations,” which refers mainly to organizational aspects of EA 17 .…”
Section: Introductionmentioning
confidence: 99%